Kewenangan KPK Untuk Menyidik Anggota TNI Bersama-Sama Dengan Sipil Secara Koneksitas - Gaol, Yulinda Regina C. Lumban; Syahrir, Alvi; Ikhsan, Edy; Trisna, Wessy (Jurnal Ilmu Hukum, Humaniora dan Politik, 2024)
Based on article 42 of Law Number 30 of 2002, KPK is given authority to coordinate and control investigation and prosecution of criminal cases of corruption carried out jointly by persons subject to the General and Military Court. However, KPK encounters problems in investigating TNI members together with civilians, as happened in the Basarnas case. This normative legal research uses statute approach and conceptual approach, in order to provide a view for harmonization of regulations related to the KPK's connectivity authority. The results show that it is necessary to change the definition of "military criminal offenses" in Military Court Bill, statutory regulations related to organizational structure of KPK and origin of institutions where KPK Investigators/Prosecutors come from, which can only be filled by National Police, Prosecutors, and Special Civil Servant. It is necessary for KPK to have a special Deputy for handling connectivity cases and Investigators who come from military.